Current Perspectives on the Archaeology of African Slavery in Latin America - Funari, Pedro (Springer, 2015)
This edited volume aims at exploring a most relevant but somewhat neglected subject in archaeological studies, especially within Latin America: maroons and runaway settlements. Scholarship on runaways is well established and prolific in ethnology, anthropology and history, but it is still in its infancy in archaeology. A small body of archaeological literature on maroons exists for other regions, but no single volume discusses the subject in depth, including diverse eras and geographical areas within Latin American contexts. Thus, a central aim of the volume is to gather together some of the most active, Latin American maroon archaeologists in a single volume. This volume will thus become an important reference book on the subject and will also foster further archaeology research on maroon settlements. The introduction and comments by senior scholars provide a wide-ranging and comprehensive analysis of runaway archaeology that will help to indicate the global importance of this research.